Knowledge and Healthy Behavior of Children Towards Correct Tooth Brushing Skills Class (IV) Student at State Elementary School in South Jakarta - Pudentiana Rr. R. E.; Siti Nurbayani Tauchid; Jusuf K.; Ita Astit Karmawati (GoAcademica Research & Publishing, 2022)
Tooth and mouth disease, a dental health problem in the community, is in the tooth-supporting tissue (periodontal disease) and dental/dental cavities. The causes of dental caries include food consumption, dental maintenance, and the teeth’ condition. In Indonesia, dental caries in children is a very important and major problem of dental and oral diseases. The survey conducted by the Indonesian Dental Health Foundation (YKGI) in 2003 on children in Jakarta showed that 70% suffered dental caries and gum inflammation. Tooth and mouth disease due to inflammation is ranked 10th in Indonesia. This study aims to determine the effect of knowledge and healthy behavior of upper (IV) elementary school students on good and correct tooth brushing skills and specifically to determine the level of knowledge and health behavior of children before and after being given good brushing and treatment skills right, to find out the difference in knowledge before and after being given the treatment of good and correct tooth brushing skills and to determine the differences in healthy behavior of children before and after being given the treatment of good and proper brushing skills.